KONTESTASI WACANA FIGUR KEMANDIRIAN PEREMPUAN DALAM BELENGGU MASYARAKAT PATRIARKAL PADA FILM YUNI - Aini, Syarifah Nur; Akalili, Awanis (Universitas Gadjah Mada, 2024)
The patriarchal culture that constructed by society brought women being in spaces full of restraints. There is an act of deconstruction of patriarchal culture which is carried out through film as a mass communication medium. One of the films that shows the empowerment of women in fighting the patriarchal environment is Yuni film. Yuni film shows the condition of the people who are very close to patriarchal culture. Until these conditions place women in marginalized and disadvantageous positions. Some of the narrations and visualizations in Yuni film show that there is women who are able to develop and have principles in the midst of conditions full of patriarchy. The purpose of this study is to explore the representation of empowered women presented through Yuni film. The research method used is content analysis with Teun A. van Dijk's critical discourse analysis model. Meanwhile, data collection was carried out by observing the scenes and narration in Yuni film. The discourse that is built about empowered women is shown by characters, characterizations, dialogues, properties and so on which is the focus of this research process. The things that are presented related to identity as an empowered woman become a potential that is focused on in Yuni film.